Autologous Induced Pluripotent Stem Cell–Based Cell Therapies: Promise, Progress, and Challenges. Issue 3 (16th March 2021) - Madrid, Marinna; Sumen, Cenk; Aivio, Suvi; Saklayen, Nabiha
Abstract: The promise of human induced pluripotent stem cells (iPSCs) lies in their ability to serve as a starting material for autologous, or patient‐specific, stem cell–based therapies. Since the first publications describing the generation of iPSCs from human tissue in 2007, a Phase I/IIa clinical trial testing an autologous iPSC‐derived cell therapy has been initiated in the U.S., and several other autologous iPSC‐based therapies have advanced through various stages of development. Three single‐patient in‐human transplants of autologous iPSC‐derived cells have taken place worldwide. None of the patients suffered serious adverse events, despite not undergoing immunosuppression. These promising outcomes support the proposed advantage of an autologous approach: a cell therapy product that can engraft without the risk of immune rejection, eliminating the need for immunosuppression and the associated side effects. Despite this advantage, there are currently more allogeneic than autologous iPSC‐based cell therapy products in development due to the cost and complexity of scaling out manufacturing for each patient. In this review, we highlight recent progress toward clinical translation of autologous iPSC‐based cell therapies. We also highlight technological advancements that would reduce the cost and complexity of autologous iPSC‐based cell therapy production, enabling autologous iPSC‐based therapies to become a more commonplace treatment modality for patients. © 2021 The Authors.